IS THERE AN ASSOCIATION BETWEEN OBSTRUCTIVE SLEEP APNEA AND CEREBROVASCULAR INSULT? - Stamenković, Zoran; Pejcic, Tatjana; Krtinic, Dane; Topalovic, Marija; Jovanovic, Hristina; Trajkovic, Hristina; Kutlesic Kurtovic, Dusanka (Acta medicae Medianae, 2022)
Obstructive sleep apnea (OSA) is highly prevalent in general population and has a bidirectional association with cerebrovascular insult (CVI), one of the leading causes of global morbidity and mortality. Untreated severe OSA doubles the risk for CVI. OSA may be associated with an increase of all-cause mortality and it may impair neurological outcome in CVI patients. Pathophysiological basis of the association and the possibilities of prevention and improvements of outcomes require further evaluation. Continuous positive airway pressure (CPAP) therapy during sleep is associated with a reduced risk of CVI in OSA patients, but the results are inconsistent. Treatment of post CVI OSA patients with CPAP therapy is recommended as part of the elimination of several risk factors involved in pathogenesis of CVI.
Keywords: obstructive sleep apnea, cerebrovascular insult, continuous positive airway pressure therapy